This is the year I put my financial life in order - Schwartz, John (New York : Avery, an imprint of Penguin Random House, 2018)
Describes the author's personal journey from near financial ruin to full financial literacy, in a book that includes advice on investments, retirement, insurance, and wills.
Includes bibliographical references (pages 263-293) and index.
Keywords: Finance, Personal; Personal finance